História da educação pública : em revista (1989-2006) - Tibaldi, Fatima Maria Melo Barbosa (2008)
This research, entitled “History of Public Education in Review”, has as its main objective to conduct a quantitative and qualitative study of the Public Education Journal of the Graduate Program in Education of the Federal University of Mato Grosso. The theme is a milestone that marks the beginning of contemporary studies, carried out in the Education and Memory Research Group (GEM), since the Journal is the oldest vehicle for the dissemination of academic knowledge within the UFMT Graduate, both in the production of knowledge, as in the development of research and its circulation in the academic sphere. The time frame of the study refers to the years 1989-2006, aiming to cover the entire period of circulation of the Journal as a category of analysis. We sought support in Bourdieu, which analyzes the relationship between the notion of symbolic capital, scientific field and field. seeking to understand its position in the structure of power relations in the social space. The methodology adopted is that of the historical approach, and the empirical universe was limited not only to the Journal's numbers, and the collection of historical documents deposited in the archives of the UFMT Graduate Program in Education, such as the Reports, Letters of Teachers and Coordinators of existing lines of research in the Program, Minutes and Legislation. A bibliographic survey was also conducted in the collections of the Central Library of UFMT and in the sector of the Institute of Education. Throughout the process, from the origin of this journal to the present day, many changes regarding the methodological technical advances and educational thematic ones prevail, prevailing only its editorial policy.